The Political Influence of Islam in Belgium - Castaño Riaño, Sergio (PARTECIPAZIONE E CONFLITTO, 2014)
Belgium is one of the Western European countries in which Muslims have reached more relevance. The immigration process initiated in 1960s brought thousands of people from Turkey and from the Arab World to the major cities of the country. As consequence of their cultural and religious particularities Muslims were progressively claiming their own space in public life. Then, in the analysis of the Muslim political participation in Belgium two stages must be differentiated: The first one dominated by the delegates of the Arabs embassies; and the second one, when the Saudi influence decreased in 1990s giving rise to the emergence of other Islamic groups whose activities were totally involved with the real concerns of Muslims in Belgium. However, after several decades, the impact of the Islamic political activity is still low compared with the social presence of Muslims in the country.